Kekerasan Dalam Rumah Tangga (KDRT) Sebagai Salah Satu Alasan Terjadinya Cerai Gugat Di Pengadilan Agama Kelas 1A Padang - Windi Asmarianti; Elwidarifa Marwenny; Yulia Risa (LPPM Universitas Dharma Andalas, 2022)
This journal discusses whether the factors that are the reasons for the divorce, how the forms of domestic violence are the reasons for divorce, and how the settlement process for divorce in Padang Class 1A Religious Court. This journal uses empirical methods which are juridical sosilogis (Sociological Research). The data sources used are primary and secondary data sources, and interviews with related parties in this study. Based on the results of research and data analysis, it is known that the factors that cause divorce are due to lack of harmony in the household, jealousy, polygamy, moral crisis, forms of domestic violence, namely psychological violence and economic violence such as snapping, and not making a living.